Prolonged Neuropsychological Deficits, Central Nervous System Involvement, and Brain Stem Affection After COVID-19—A Case Series - Groiss, Stefan Jun; Balloff, Carolin; Elben, Saskia; Brandenburger, Timo; Müttel, Tomke; Kindgen-Milles, Detlef; Vollmer, Christian; Feldt, Torsten; Kunstein, Anselm; Ole Jensen, Björn-Erik; Hartung, Hans-Peter; Schnitzler, Alfons; et al. (Frontiers in Neurology, 2020)
Objective: The affection of both the peripheral (PNS) and central nervous system (CNS) by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been assumed to play a direct role in the respiratory failure of patients with Corona virus disease 2019 (COVID-19) through affection of medullary cardiorespiratory centers resulting in neurological complications and sequelae. Methods: We used a multimodal electrophysiological approach combined with neuropsychological investigations to study functional alteration of both the PNS and CNS in four patients with severe COVID-19. Results: We found clear electrophysiological evidence for affection of both the PNS and CNS, and particularly affection of brain stem function. Furthermore, our neuropsychological investigations provide evidence of marked impairment of cognition independent of delirium, and persisting and outlasting the duration of acute infection with SARS-CoV-2. Conclusion: This case series provides first direct electrophysiological evidence for functional brain stem involvement in COVID-19 patients without evident morphological changes supporting the notion of the brain stem contributing to respiratory failure and thus promoting severe courses of the disease. Moreover, sustained neuropsychological sequelae in these patients may be of particular psychosocial and possibly also economic relevance for society.